Interpretación, aplicación y análisis del impacto financiero del régimen impositivo para microempresas -caso Comercial CTC de Alex Toapanta - Cerezo Murillo, Marjorie Rosalva (2021)
¨CTC¨ Tecnologías Computacionales, is dedicated to provide the city of Babahoyo, computer equipment, technology, and computer education services, since March 24 of 1994, its objective or mission, is to be leaders in marketing and distribution of technology products and maintenance thereof, in teaching services with computer training courses, hosting and data protection consulting. Becoming a micro-company that not only offers products and services, since it provides a global solution to companies, professionals, business managers and individual users locally and nationally. CTC Tecnologías Computacionales, currently lives with the problem of the lack of adequate tax planning, which has led to the same, not handle in a timely manner the profits generated by the business, and in turn, do not have a reliable source to turn to when evaluating a new investment or purchase of goods, prohibiting him to know the true profitability of its activity. The purpose of this research work is to highlight the importance of proper business planning and to evaluate its relevance or impact when applied correctly in the tax area. The case study is framed under the research subline "FINANCIAL MANAGEMENT, TAXATION AND SOCIAL COMMITMENT" framed and established in the research lines of the School of Accounting, Auditing and Finance.